Influence of heavy oil components and optimal magnetic nanocatalysts on the heavy oil upgrading by microwave-assisted - Parya Torkaman; Ramin Karimzadeh; Arezou Jafari (Results in Engineering)
One of the latest thermal techniques to upgrade heavy oil is microwave heating, which increases molecular fluctuations and movements to raise the oil temperature and decrease its viscosity. The research aimed to determine the influence of process variables, such as the type and quantity of nanocatalyst, and the duration of irradiation. The effect of these parameters was investigated to establish the optimum conditions. Iron oxide-manganese oxide hybrid nanocatalyst (2:1 ratio, 0.5 % wt, 400 W, 4 min) had the most significant decline in viscosity and breakage of heavy compounds. In the mentioned suitable conditions, the effect of the type of oil was investigated, and the viscosity decrease for O1 and O2 oil samples was 53 % and 23 %, respectively. In addition, changes in the functional group indices were examined under suitable conditions, revealing that the O1 oil sample, containing more polar compounds like asphaltene, underwent a greater impact from the process and underwent more upgrading compared to the O2 oil sample. The aromatic and sulfoxide functional groups decreased by 21 % and 72 %, respectively, in the O1 oil sample, and by 14 % and 60 % in the O2 oil sample. Furthermore, the level of asphaltene decreased by 15 % under optimal wave radiation conditions and by 44 % in the presence of nanocatalysts under wave radiation. A study assessed the performance of nanocatalysts after initial reuse. The first application showed great upgrading in heavy oil; a 31 % reduction in viscosity, followed by a 26 % decrease. It indicates a slight loss in efficiency due to aggregation or degradation.